2021
DOI: 10.3390/en14051436
|View full text |Cite
|
Sign up to set email alerts
|

Application of MICMAC, Fuzzy AHP, and Fuzzy TOPSIS for Evaluation of the Maintenance Factors Affecting Sustainable Manufacturing

Abstract: This paper presents an empirical study on the impact of maintenance function on more sustainable manufacturing processes. The work methodology comprises four stages. At first, ten factors of maintenance activities from a sustainable manufacturing point of view were identified. Then, in the second stage, the matrix of crossed impact multiplications applied to a classification (MICMAC) was carried out to categorize these factors based on their influence and dependence values. In the third stage, the criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 122 publications
0
26
0
1
Order By: Relevance
“…In this regard, the combination of ISM-MICMAC with DEMATEL (e.g., Mishra, 2020;Yadav et al, 2020) to present a casual model is the most popular one. Moreover, using an analytical hierarchical process (AHP) (e.g., or Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) (e.g., Jasiulewicz-Kaczmarek et al, 2021) besides the ISM-MICMAC to evaluate the importance of the identified criteria and factors have been designed by other scholars recently. Thirdly, many scholars have employed Structural Equation modelling (SEM) to validate the conceptual model emanated from the ISM-MICMAC approach (e.g., Khaba et al, 2020;Ullah & Narain, 2020).…”
Section: Quantitative Research Design: Micmac-ismmentioning
confidence: 99%
“…In this regard, the combination of ISM-MICMAC with DEMATEL (e.g., Mishra, 2020;Yadav et al, 2020) to present a casual model is the most popular one. Moreover, using an analytical hierarchical process (AHP) (e.g., or Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) (e.g., Jasiulewicz-Kaczmarek et al, 2021) besides the ISM-MICMAC to evaluate the importance of the identified criteria and factors have been designed by other scholars recently. Thirdly, many scholars have employed Structural Equation modelling (SEM) to validate the conceptual model emanated from the ISM-MICMAC approach (e.g., Khaba et al, 2020;Ullah & Narain, 2020).…”
Section: Quantitative Research Design: Micmac-ismmentioning
confidence: 99%
“…Numerous studies have adopted different multi-criteria decision-making methods such as fuzzy AHP, fuzzy TOPSIS, fuzzy VIKOR, etc., in solving different uncertain problems. Kaczmarek et al [43] used MICMAC, fuzzy AHP, and TOPSIS methods to select the most critical factors affecting sustainable manufacturing. Prakash et al [13] applied the fuzzy AHP method to prioritize the barriers in reverse logistics implementation in the Indian electronics industry.…”
Section: Methods Choicementioning
confidence: 99%
“…The fuzzy analytic hierarchy process (FAHP) combines fuzzy theory and analytical hierarchy process (AHP) and is good at dealing with fuzzy decision problems [ 32 , 33 , 34 ]. Saaty [ 35 ] proposed AHP in 1980 to deal with decision-making problems with multiple criteria in uncertain environments.…”
Section: Theoretical Backgroundmentioning
confidence: 99%